Flapless application of enamel matrix derivative in periodontal retreatment: A multicentre randomized feasibility trial. (9th March 2021) - Jentsch, Holger F. R.; Roccuzzo, Mario; Pilloni, Andrea; Kasaj, Adrian; Fimmers, Rolf; Jepsen, Søren
Abstract: Aim: To investigate the potential benefit of enamel matrix derivative (EMD) as adjunct to re‐instrumentation of residual pockets persisting after steps 1 and 2 of periodontal therapy. Material and Methods: 44 adult patients participated in a multicentre feasibility randomized clinical trial with split‐mouth design. They had presented at re‐evaluation after initial non‐surgical periodontal therapy (steps 1 and 2 of periodontal therapy) for generalized periodontitis with at least 2 teeth with residual probing pocket depths (PPD) ≥5 and ≤8 mm, with bleeding on probing (BOP). Two teeth with similar PPD were randomized to receive re‐instrumentation either with (test) or without (control) adjunctive flapless administration of EMD. Differences in the changes of PPD and BOP from baseline to 6 and 12 months were analysed, and the frequencies of pocket closure (PPD ≤4 mm and no BOP) compared. Results: For the primary outcome "change of mean PPD after 6 months, " a significant additional benefit of 0.79 ± 1.3 mm ( p < .0001) could be observed for the test group. At 12 months, this difference could be maintained (0.85 ± 1.1 mm; p < .0001). The frequency of pocket closure in the test group was 69% at 6 and 80% at 12 months and significantly higher than in the control group with 34% and 42%, respectively ( p < .01). Conclusions: The results of the present feasibility study indicate a benefit of adjunctive EMD during non‐surgical retreatment (step 3 of periodontal therapy) of residual deep pockets.